2017
DOI: 10.1186/s13075-016-1218-4
|View full text |Cite
|
Sign up to set email alerts
|

Persistent stromal fibroblast activation is present in chronic tendinopathy

Abstract: BackgroundGrowing evidence supports a key role for inflammation in the onset and progression of tendinopathy. However, the effect of the inflammatory infiltrate on tendon cells is poorly understood.MethodsWe investigated stromal fibroblast activation signatures in tissues and cells from patients with tendinopathy. Diseased tendons were collected from well-phenotyped patient cohorts with supraspinatus tendinopathy before and after sub-acromial decompression treatment. Healthy tendons were collected from patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
107
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(114 citation statements)
references
References 29 publications
6
107
1
Order By: Relevance
“…This may help to explain the capacity of antibodies against widely expressed antigens to drive joint inflammation. Recent research from Oxford University suggested that chronic tendinopathy was due to an initial (and supposedly resolved) insult, which led nonetheless to fibroblasts acquiring a fibrotic and hyper‐responsive phenotype . As remarked above, the altered fibroblast phenotype may be explained in part by differentiation or expansion of a fibroblast subpopulation.…”
Section: Role Of Stromal Memory In Infection and Chronic Inflammatorymentioning
confidence: 96%
See 4 more Smart Citations
“…This may help to explain the capacity of antibodies against widely expressed antigens to drive joint inflammation. Recent research from Oxford University suggested that chronic tendinopathy was due to an initial (and supposedly resolved) insult, which led nonetheless to fibroblasts acquiring a fibrotic and hyper‐responsive phenotype . As remarked above, the altered fibroblast phenotype may be explained in part by differentiation or expansion of a fibroblast subpopulation.…”
Section: Role Of Stromal Memory In Infection and Chronic Inflammatorymentioning
confidence: 96%
“…This will obviously due be partly to the adaptive immune response, but as this review has shown, the effect on other cell types, and so the tissue or even organism as a whole, are not to be dismissed. Didierlaurent and colleagues discussed the effects of repeat lung infection [74], while Dakin et al hypothesized [31] and later confirmed [36] that an acute injury event may prepare tendons for chronic tendinopathy and fibrosis upon a second insult. Such concepts show a clear clinical relevance to repeat challenge of innate cells.…”
Section: The Clinical Significance Of Stromal Memorymentioning
confidence: 99%
See 3 more Smart Citations